Ts. Dr. Farhan first woman appointed as technical panel member of fatwa by Muslim Professional Japan Association MPJA - Azizul Helmi, Sofian (2021)
GAMBANG, 27 May 2021 - The Halal Assurance and Halal Certification Management System has been recognised globally and has become a benchmark for other countries worldwide.